Physiological responses of Cucurbita pepo seeds to cadmium and copper stress: Differential impacts on reserve mobilization, metabolic efficiency, and growth - Smail Acila; Nora Allioui; Samir Derouiche (PLoS ONE, 2026)
Heavy metal contamination poses a significant threat to agricultural productivity. This study investigated the physiological and biochemical responses of Cucurbita pepo seeds to cadmium (Cd) and copper (Cu) stress (100–200 µM) during germination. Although germination rates remained high (86.67–93.33%), seed vigor indices declined significantly under metal stress. Cadmium exhibited stronger growth inhibition, reducing total seedling length by 63.02% at 200 µM, whereas copper primarily affected biomass accumulation, reducing the seedling weight-based vigor index (SVI W ) by 40.4%. Biochemical analyses revealed metal-specific impacts on reserve mobilization. Cadmium exposure (200 µM) decreased soluble sugars in cotyledons by 16%, while maintaining protein content at 106% of control levels, indicating inhibition of protein degradation and impaired reserve utilization. In contrast, copper at 100 µM increased cotyledonary sugars by 63%, reflecting its dual role as both a micronutrient and stressor. Principal component analysis confirmed the greater toxicity of Cd, which explained 79.7% of the variance in metabolic disruption. These findings demonstrate that cadmium consistently impairs seedling establishment by disrupting nutrient mobilization pathways, while copper exhibits concentration-dependent effects, being stimulatory at low concentrations but inhibitory at higher levels. This study provides crucial insights into heavy metal phytotoxicity mechanisms and underscores the importance of monitoring metal pollution in agricultural systems to enhance crop resilience.